Chord-based Quantum Botnet Research - Wang Xin-Liang; Lu Nan; Gao Qing-Hua (Institute of Advanced Engineering and Science, 2014)
In order to make the controller better to master the botnet, the traditional chord-based botnets ensure that all adjacent nodes can maintain the periodic communication so that the routing table of every node could keep accurate and efficient. The periodic communication behavior will also increase the risk of exposure of the traditional chord-based botnets. Once one of the peers is captured by network security device, more peers will be captured based on periodic communication behavior of chord-based botnets that leads to affect the botnet robustness. For the aforementioned problems in the traditional chord-based botnet, this paper will construct a quantum botnet control platform based on the improved B92 protocol. The in-depth analysis showed that the infected hosts in the chord-based quantum botnet can more quickly be increased, and can maintain a larger scale compared with the traditional chord-based botnet. So the chord-based quantum botnet owns better robustness and stability.